2013
DOI: 10.1177/014556131309200118
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma Metastatic to the Larynx: A Case Report

Abstract: Malignant melanoma of the larynx is a rare cancer that can appear as a primary tumor or as a metastasis from a cutaneous head and neck primary. To the best of our knowledge, only 60 cases of primary laryngeal melanoma have been reported in the world literature. Melanomas metastatic to the larynx are even more rare, as only 24 cases have been previously reported. Survival is poor, and recurrence is uncommon. We describe a new case of a malignant melanoma metastatic to the larynx, which represents the first such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Characteristics of the 37 included patients are shown in Table I . All were adults aged 21 to 73 years with a 1.6:1 male to female ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the 37 included patients are shown in Table I . All were adults aged 21 to 73 years with a 1.6:1 male to female ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Most articles identified after the search were not eligible for analysis, due to the fact that they referred either to the wrong disease, to primary mucosal melanoma or to laryngeal metastases of another condition. To our knowledge, this is the first article on this topic after Arabi Mianroodi et al reported a similar case in 2013 and Santos RS et al documented a case series of four patients in 2016 [15,16].…”
Section: Discussionmentioning
confidence: 70%
“…The mean patient age was 56-years-old and average time period to larynx metastasis was 4.3 years. Interestingly, most patients were men (19 out of 24 patients, 79.16%), while women represented only 20.84% of patients (5 out of 24 cases) [15,16,33,[44][45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%